2018
DOI: 10.1111/aogs.13327
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences and depressive symptomatology among pregnant women

Abstract: ACE was commonly reported. ACE and depressive symptomatology in late pregnancy were strongly associated in a dose-response manner. Women with several ACEs had high odds of depressive symptomatology in late pregnancy and were more likely to report depressive symptoms both in late pregnancy and postpartum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 37 publications
3
26
0
Order By: Relevance
“…Thomas et al (2018) found women with a history of four or more ACEs to have altered HPA (hypothalamic-pituitary-adrenal) axis functioning (e.g., 2.5 times higher awakening cortisol levels) during pregnancy than those who reported none. To date, much of the psychological literature has focused on the dose-response association between ACEs and depressive symptoms during and following pregnancy (Ångerud et al, 2018;Chung et al, 2008), whereas no studies have examined the associations between ACEs and pregnancy-specific stress. However, the "wear and tear" process of ACEs (e.g., altered HPA functioning) and the hindering of the acquisition of healthy coping strategies in the face of adversity, may exacerbate pregnancy-specific stress, especially among women with lack of adequate resources.…”
Section: Childhood Experiences and Pregnancymentioning
confidence: 99%
“…Thomas et al (2018) found women with a history of four or more ACEs to have altered HPA (hypothalamic-pituitary-adrenal) axis functioning (e.g., 2.5 times higher awakening cortisol levels) during pregnancy than those who reported none. To date, much of the psychological literature has focused on the dose-response association between ACEs and depressive symptoms during and following pregnancy (Ångerud et al, 2018;Chung et al, 2008), whereas no studies have examined the associations between ACEs and pregnancy-specific stress. However, the "wear and tear" process of ACEs (e.g., altered HPA functioning) and the hindering of the acquisition of healthy coping strategies in the face of adversity, may exacerbate pregnancy-specific stress, especially among women with lack of adequate resources.…”
Section: Childhood Experiences and Pregnancymentioning
confidence: 99%
“…[11][12][13][14][15][16][17] Less studied but of great interest is the potential impact of ACEs on maternal health outcomes during pregnancy. A small but growing body of literature suggests that ACEs are associated with increased mental health risks during pregnancy, including higher depressive symptoms, [18][19][20][21] anxiety, 22,23 suicidality, 24,25 and substance use. 20,[26][27][28] In addition, a history of ACE exposure is associated with higher rates of psychosocial difficulties 29 and IPV in pregnancy, 20,[30][31][32] which contribute to poor mental health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Another study also similarly determined that pregnant women with ACEs showed high levels of depressive symptoms. 22 One of the most common negative emotions during pregnancy is anxiety. 35 Adverse childhood experiences increase pregnancy-related anxiety, causing negative behaviors in pregnant women such as smoking and alcohol use and threatening maternal and fetal health.…”
Section: Discussionmentioning
confidence: 99%
“…15,20 Moreover, the weaker defense systems of women who have adverse childhood experiences 21 are seen as a strong risk factor in development of depressive symptoms during pregnancy. 22 Therefore, the effects of ACEs on psychosocial health in pregnancy should be evaluated and emphasized. 4 In the literature, it is emphasized that parenthood may be a difficult task for individuals with ACEs.…”
Section: Introductionmentioning
confidence: 99%